Interprofessional Collaboration in the Mental Health Services in Norway - Ellen Andvig; Jonn Syse; Elisabeth Severinsson (Hindawi Limited, 2014)
The aim of this study was to describe and interpret interprofessional collaboration between healthcare professionals (HCPs) working at the district psychiatric centre (DPC) and employed in community mental health care (CMHC) using a dialogue-oriented co-operative approach. Data were collected by means of multistage focus groups and qualitative content analysis was performed. The main theme "development of interprofessional collaboration by means of organisational strategies and interactional styles" encompassed the following categories: "improved communication skills," "developing structures for coordination and responsibility" and " increased professional insight into the values and conditions necessary for decision-making." In conclusion, more attention should be paid to leadership in terms of coordination and feedback. The HCPs must be acknowledged, understood and strengthened in their work to improve the quality of CMHC. Finally, we recommend that a range of organisational and administrative models of care be used in order to support improvement work.